2019
DOI: 10.1360/n972018-01178
|View full text |Cite
|
Sign up to set email alerts
|

Sr/Eu cation doping and thermoelectric properties of the compound Ca<sub>9</sub>Zn<sub>4.5</sub><sub>−</sub><sub><italic>δ</italic></sub>Sb<sub>9</sub> (0<<italic>δ</italic><0.5)

Abstract: 摘要 作为一种非常有前景的热电材料, Ca 9 Zn 4.5−δ Sb 9 (0<δ<0.5)相较于其他材料有着成本低、环保高效等优势. 以 往研究表明间隙金属元素在该体系中起着关键作用, 然而由于其狭窄的域值范围制约了Ca 9 Zn 4.5−δ Sb 9 的性质调控. 本文用原子半径更大的阳离子Sr/Eu来取代少量Ca, 使其Seebeck系数和电学性质得以同步增强, 得到了间接调控 间隙原子的结果. 载流子测试表明, 载流子浓度有轻微降低, 而载流子迁移率有着明显提升, 这与增大的晶体热导 性质都表明晶体结构发生了明显变化. 对Ca 9−x Sr x Zn 4.5−δ Sb 9 (0<δ<0.5)系列进行了单晶X射线衍射测试, 结果表明随 Sr含量增大晶格参数有增大趋势, 间隙Zn原子浓度上升, 材料热电性能得到协同优化. 最终掺杂样品中, Ca 8.2 Eu 0.8 Zn 4.5−δ Sb 9 在873 K得到最大热电优值(ZT)约为0.81.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…20 In Sr-doped Ca 9 Zn 4+x Sb 9 series, increased concentration of interstitial Zn atoms and thereby improved carrier mobility were found due to the expanded anionic framework. 21 By substituting the rare-earth elements on CaAgSb, interesting phase transition from TiNiSi type to LiGaGe type occurred, alongside the optimized electronic bands and improved TE performance. 22 It is reported that the introduction of the smaller Li on the Ca site in Ca(Zn 0.4 Ag 0.2 ) Sb led to the shrinkage of interlayered distances and the optimized orbital alignment, accompanied by a high zT value of 1.3.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In Sr-doped Ca 9 Zn 4+x Sb 9 series, increased concentration of interstitial Zn atoms and thereby improved carrier mobility were found due to the expanded anionic framework. 21 By substituting the rare-earth elements on CaAgSb, interesting phase transition from TiNiSi type to LiGaGe type occurred, alongside the optimized electronic bands and improved TE performance. 22 It is reported that the introduction of the smaller Li on the Ca site in Ca(Zn 0.4 Ag 0.2 ) Sb led to the shrinkage of interlayered distances and the optimized orbital alignment, accompanied by a high zT value of 1.3.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ca 9 Mn 4+ x Sb 9 was reported to crystallize in the Pnma space group, while the inclusions of rare-earth elements at Ca sites resulted in a derivative of Ca 9 Mn 4 Bi 9 ( Pbam ) with a tetrahedron-coordinated Mn splitting . In Sr-doped Ca 9 Zn 4+ x Sb 9 series, increased concentration of interstitial Zn atoms and thereby improved carrier mobility were found due to the expanded anionic framework . By substituting the rare-earth elements on CaAgSb, interesting phase transition from TiNiSi type to LiGaGe type occurred, alongside the optimized electronic bands and improved TE performance .…”
Section: Introductionmentioning
confidence: 99%